Chemical Components, Biological Activities, and Toxicological Evaluation of the Fruit (Aril) of Two Precious Plant Species from Genus Taxus. Issue 12 (15th December 2017) - Li, Na; Pan, Zheng; Zhang, Dan; Wang, Hua‐Xing; Yu, Bao; Zhao, Sheng‐Ping; Guo, Jia‐Jia; Wang, Jian‐Wei; Yao, Ling; Cao, Wei‐Guo
Abstract : The fruit (aril) of the endangered genus Taxus plants is an abandoned herbal resource. Traditionally, people enthusiastically focus on its bark, its renewable, tremendous arils fall into the soil with seeds after they are mature. The present research investigated the fruit of two species from the genus Taxus, Taxus chinensis var. mairei, and Taxus media, with regards to their antioxidant and antihyperglycaemic activities, safety, and bioactive constituents. Results showed that T . chinensis var. mairei and T . media both had certain biological activities with T . chinensis var. mairei better in antioxidant activity and T . media better in antihyperglycaemic activity. Correlation analysis revealed that the differences in bioactivities depended on content of their mainly chemical components. The mice acute oral toxicity test indicated that the methanol extracts of the two biotypes of Taxus were safe. And nineteen compounds were tentatively assigned from the two varieties, via tandem mass spectrometry using a LC‐ESI‐Q‐TOF‐MS instrument, which included phenols, flavonoids, and terpenes. These results indicate a possible application of Taxus fruit extracts in various fields like in food industry, however, this still needs further investigations. Abstract :